Moisture Barrier Composites Made of Non‐Oxidized Graphene Flakes. Issue 26 (26th February 2015) - Kim, Jungmo; Song, Sung Ho; Im, Hyeon‐Gyun; Yoon, Gabin; Lee, Dongju; Choi, Chanyong; Kim, Jin; Bae, Byeong‐Soo; Kang, Kisuk; Jeon, Seokwoo
<x xml:space="preserve">Abstract</x> Graphene flakes (GFs) with minimized defects and oxidation ratios are incorporated into polyethylene (PE) to enhance the moisture barrier. GFs produced involving solvothermal intercalation show extremely low oxidation rates (3.17%), and are noncovalently functionalized in situ, inducing strong hydrophobicity. The fabricated composite possesses the best moisture barrier performance reported for a polymer–graphene composite.